Effect of Service Quality on Patient Satisfaction at Graha Juanda Hospital in Bekasi - Nurhadi, Ahmad (Jurnal Office, 2020)
To improve health services to the community, RS. Graha Juanda Bekasi, as a referral for patients in Bekasi and its surrounding areas, continues to make improvements. This study aims to determine the effect of service quality on patient satisfaction at Graha Juanda Hospital in Bekasi. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this research variable Service Quality obtained an average score of 3.40 with good criteria. The patient satisfaction variable obtained an average score of 3.82 with good criteria. Service quality has a significant effect on patient satisfaction with the regression equation Y = 7.695 + 0.897X, and a correlation value of 0.784 or strong with a determination of 61.5%. Hypothesis testing obtained a significance of 0.000 <0.05.